2010
DOI: 10.1186/1752-0509-4-76
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel data integration resource for breast cancer study

Abstract: BackgroundBreast cancer is one of the most common cancer types. Due to the complexity of this disease, it is important to face its study with an integrated and multilevel approach, from genes, transcripts and proteins to molecular networks, cell populations and tissues. According to the systems biology perspective, the biological functions arise from complex networks: in this context, concepts like molecular pathways, protein-protein interactions (PPIs), mathematical models and ontologies play an important rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 42 publications
0
67
0
Order By: Relevance
“…Among the 20 genes found most significantly overexpressed in breast tumors by our test, 11 were inside genesets of C2 relative to breast cancers, and outside all genesets relative to lung tumors: EFHD1, IRX5, MUCL1, PRLR, PTGER3, RGL2, TRIL, TRPS1, VAV3, WWP1, ZG16B. Seven of these genes can be found in the G2SBC database [48] and for 10 out of 11, we have found at least one reference relating it to breast cancer. Conversely, among the most significant genes for lung tumor, the following were found in C2 genesets related to lung and not in those related to breast: ALDH3B1, DARS, PRPSAP2, FAM96B, MBIP, LRRC20.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 20 genes found most significantly overexpressed in breast tumors by our test, 11 were inside genesets of C2 relative to breast cancers, and outside all genesets relative to lung tumors: EFHD1, IRX5, MUCL1, PRLR, PTGER3, RGL2, TRIL, TRPS1, VAV3, WWP1, ZG16B. Seven of these genes can be found in the G2SBC database [48] and for 10 out of 11, we have found at least one reference relating it to breast cancer. Conversely, among the most significant genes for lung tumor, the following were found in C2 genesets related to lung and not in those related to breast: ALDH3B1, DARS, PRPSAP2, FAM96B, MBIP, LRRC20.…”
Section: Resultsmentioning
confidence: 99%
“…Since we used a breast cancer cell line, we compared the list of genes modulated by miR-3134 with those commonly mis-regulated in breast cancer using the G2SBC (The Genes-to-Systems Breast Cancer (G2SBC) Database) database and found that 50 out of 220 genes (22.7%) are shared between the two lists. 19 These observations hint that miR-3134 regulated ARE transcriptome subset and, thus, levels of several cancer related genes may lead to breast cancer development/progression (Fig. 2C).…”
Section: Resultsmentioning
confidence: 99%
“…All of this data regarding the ZNF expression level suggest the importance of ZNF as a biomarker candidate in different tumor types. ZNF 510 has been a well-known biomarker for breast cancer as suggested in a studies conducted in the year 2010 and 2011 [88,89]. A recent study (2011) for the first time reported the role of ZNF 510 as a potential biomarker for OSCC by comparing the salivary proteomic profiles of OSCC patients with the control group.…”
Section: Zinc Finger Protein 510 As a Novel Biomarkermentioning
confidence: 99%